1996
DOI: 10.1021/jp951722t
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Stability of M−H2 Complexes

Abstract: The potential stability of van der Waals complexes M−H2 (M = Li, Be, B, C, Na, Mg, Al, Si) is assessed using quadratic configuration interaction and large basis sets. It is found that the alkali metals and alkaline earths form very weak complexes in their ground states, but much stronger complexes in their (p) excited states. The elements B, Al, C, and Si form both linear (C∞v) and perpendicular (C2v) complexes, with greater thermodynamic stability in the latter arrangements. The complexes formed by C are like… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
75
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(80 citation statements)
references
References 30 publications
(62 reference statements)
5
75
0
Order By: Relevance
“…1. The results are in good accord with the recent study of Chaban and Gordon [19] who report a collinear van der Waals minimum at R CG vm 9X845Y 1X402Y 0 with an energy i 1 2 A H R CG vm 15 cm À1 . Also found was a van der Waals-like saddle point on the groundstate PES for the perpendicular con®guration R vts 10X66Y 1X4011Y 90 with i 1 2 A H R vts 5X6 cm À1 , again in good accord with the results of Gordon and Chaban, R CG vts 10X204Y 1X402Y 90 with i 1 2 A H R CG vts 9 cm À1 .…”
Section: Computational Prerequisitiessupporting
confidence: 92%
See 2 more Smart Citations
“…1. The results are in good accord with the recent study of Chaban and Gordon [19] who report a collinear van der Waals minimum at R CG vm 9X845Y 1X402Y 0 with an energy i 1 2 A H R CG vm 15 cm À1 . Also found was a van der Waals-like saddle point on the groundstate PES for the perpendicular con®guration R vts 10X66Y 1X4011Y 90 with i 1 2 A H R vts 5X6 cm À1 , again in good accord with the results of Gordon and Chaban, R CG vts 10X204Y 1X402Y 90 with i 1 2 A H R CG vts 9 cm À1 .…”
Section: Computational Prerequisitiessupporting
confidence: 92%
“…e 1X05 eV, that is about 0.8 eV below i 2 2 A H R asym (see Fig. 1), in good accord with 1.13 eV found by Hobza and Schleyer [15], 1.063 eV found by Boldyrev and Simons [21], and 1.054 eV reported by Chaban and Gordon [19]. No other minima were found on this PES.…”
Section: Potential Energy Surfacessupporting
confidence: 90%
See 1 more Smart Citation
“…It was found that the 1 A′ states wave function converged only with the second-order SCF (SOSCF) method. 45 The full Newton-Raphson orbital improvement (FULLNR) method was used to obtain the singlet A′′ states, both triplet A′ and A′′ states, and all C 2V excited states. 46 …”
Section: Methodsmentioning
confidence: 99%
“…We have recently discovered cyclic isomers on the lowest singlet and triplet PES of N 3 F. 51 The geometrical parameters of these stationary points and barrier heights for isomerization and dissociation were determined at the multiconfigurational self-consistent field (MCSCF) 29 level of theory using the standard 6-31G(d) basis set. 39 Relative isomer energies and barrier heights were recalculated using multireference secondorder perturbation theory (CASPT2) 45 and multireference configuration interaction (MRCI), 5 with larger 6-311G(d) and 6-311G(2d) basis sets.…”
Section: Applicationsmentioning
confidence: 99%